2007
DOI: 10.1002/adic.200790027
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Preconcentration of Copper, Nickel, Cobalt and Lead Ions Prior to Their Flame Atomic Absorption Spectrometric Determination

Abstract: Summary -A sensitive and simple method for the simultaneous preconcentration of nutritionally important minerals in real samples has been reported. The method is based on the adsorption of Cu 2+ , Ni 2+ , Co 2+ and Pb 2+ on 4-propyl-2-thiouracil (PUT) loaded on activated carbon. The metals on the complexes are eluted using 5 mL 3 M HNO 3 in acetone. The influences of the analytical parameters including pH and sample volume were investigated. The effects of matrix ions on the retentions of the analytes were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
10

Relationship

8
2

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Solution pH affects the metal binding sites of the sorbent and the metal ion chemistry in aqueous solution [34,35]. Various authors have shown that solution pH greatly influences metal biosorption by algae biomass [36][37][38][39].…”
Section: Effect Of Phmentioning
confidence: 99%
“…Solution pH affects the metal binding sites of the sorbent and the metal ion chemistry in aqueous solution [34,35]. Various authors have shown that solution pH greatly influences metal biosorption by algae biomass [36][37][38][39].…”
Section: Effect Of Phmentioning
confidence: 99%
“…The real samples were treated according to our previous publication [23][24][25][26][27] as following. The certified liver sample was also digested in the manner described below.…”
Section: Applicationmentioning
confidence: 99%
“…Fenne, spearmint and water samples were prepared as we previously reported [41][42][43]. The procedure set out in Sect.…”
Section: Pretreatment and Analysis Of Real Samplesmentioning
confidence: 99%